PENGARUH FASILITAS WISATA, HARGA DAN KEAMANAN TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA WISATA SUBAN AIR PANAS CURUP - Junensih, Silvi Anggraeni; Ratnawili, Ratnawili (Yayasan Insani Mandiri Santani, 2021)
This study aims to determine the effect of tourism facilities, price and safety on tourist visiting decision at Hot Spring Tourism of Curup. The population of this study was all tourists who are visiting atÂ Hot Spring Tourism of Curup. The sample of this study was 70 respondents. The sample was determined by using purposive sampling technique with the criteria of the respondents being visitors who were visiting at Hot Spring Tourism of Curup. The data was analyzed by using quantitative analysis (validity and reliability tests), multiple regressi on analysis, classical assumption test (multicollinearity normality) and heteroscedasticity), the ttest and the coefficient of determination. From the results of multiple regression analysis, it is found that the regression equation Y=13.251+0.251(X1)+0.279(X2)+0.539(X3).This means that the Tourism Facility ,Price and Security variables have appositive effect on visiting decisions. While from the hypothesis, thet value for Tourism Facilities (X1) is 2.480 with a significan celevel of 0.016, for Price (X2)2.249 with a significance of 0.028 and for the security variable (X3)3.783 with a significan celevel of 0.000. t test statessignifican tresults forall variables and the hypothesis accepted.The result of multiple regression analysis also shows the coefficient of determination of 0.589,which means that the variables of Tourism Facilities, Price and Security give effect on visiting decision of tourists by 58.9%,while 41.1% is influenced by other variables which are not observed in this study.